Epifit pada rumput laut di lahan budidaya desa Tumbak - Mudeng, Joppy D. (Universitas Sam Ratulangi, 2017)
The purpose of this research was to identify the types of epiphyte that attach to seaweed in cultivation area of Tumbak Village, Posumaen District, Southeast Minahasa Regency. Identifications were done directly in cultivation site owned by farmers and in Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine Science Sam Ratulangi University. Observations were conducted three times at two weeks interval. Weight of seaweed was measured to obtain data of daily growth rate. In addition, water quality was also measured in situ including dissolved oxygen, pH, temperature and salinity. Research result found there were three species of epiphyte attaching on seaweed K. alvarezii including Ulva reticulata Forsskal, Dictyota dicotoma (Hudson), and Achanthophora spicifera (J. Agardh). Seaweed tested was still clean until the end of research period and only a few of epiphyte was observed. This condition, supported by good water quality during the research period, resulted in very good growth of seaweed with a daily growth rate achieved 4.43%. Keywords: seaweed, epiphyte, daily growth rate